Bogor Message and Wasatiyyat Islam: Reviving Islamic Diplomacy and Constituting the Transnationalism of Islam - Ramadhan, Jelang (LPPM Universitas Lampung, 2022)
Bogor Message is constituting the transnationalism of Islam and reviving the importance of diplomacy based on religious consultation or even multilateralism, that concluded by prominent Islamic scholars (ulama) in the world through High-Level Constitution of World Muslim Scholars in 2018. Thus, Bogor Message is considered a form of ijma’ ulama (consensus among Islamic scholars) which will be useful for Muslim ummah (Islamic society) as a common ground depicting universal norm in regulating the attitude toward international relations (IR). Wasatiyyat Islam summed up in the Bogor Message, is the embodiment of Islamic tradition in the multi-track diplomacy where interactions between state-actors and non-state actors and utilization of tracks in diplomacy resulted in an understanding to solve ummah fundamental problems in Islamicate world through the normative religious approach. The Bogor Message is rendezvous point and unified the differences of Wasatiyyat Islam conception aimed to unite ummah in the framework of transnational Islam, taken from Al-Qur’an and Sunnah. This research article examines the principle of Wasatiyyat Islam inside Bogor Message and its functionality as soft power by using diplomacy theories. The lack of concern from ummah in other countries due to the outbreak of COVID-19 pandemic hampered the progress of Wasatiyyat Islam dissemination and remained exclusive for certain bastions of ‘moderate Islam’ countries. Though the potencies for developing and globalizing Wasatiyyat Islam could gain momentum in the post-COVID-19 world.